Consumption of human albumin in the hospitalization services of the Hospital Militar Central - Ale Quispe, Pamela E. (2022)
Objective: To evaluate the consumption of human albumin 20% in the hospitalization services of the Hospital Militar Central during the period June - December 2019. Materials and methods: Observational, descriptive, cross-sectional and retrospective research, whose sample consisted of 1139 records provided by the computer service of hospitalized patients. Results: The average age of the patients was 78.2 years, 57.8% were 80 years old or older, 63.2% were male and 55.3% had holder status. The drug was prescribed mainly in hypoalbuminemia (27.37%) and nephrotic syndrome (23.16%). The service with greater patient care was internal medicine (50%), but those of higher prescriptions of human albumin 20% were gastroenterology (1539 bottles) and internal medicine (1276 bottles), with an average of 61.6 and 13.4 bottles per person, respectively, as well as those of higher total costs (S / 173,183.67 and S / 143,588.28, respectively). Conclusion: The consumption of human albumin 20% was prescribed mainly in male patients, 80 years of age or older, with hypoalbuminemia and nephrotic syndrome, treated in the hospitalization services for gastroenterology and internal medicine of the Central Military Hospital.